Pengaruh Penerapan Model Project Based Learning terhadap Hasil Belajar Geografi Siswa Kelas XI di SMAN 14 Padang - Aini, Yunita Raitul; Ernawati, Ernawati (Lembaga Yasin AlSys, 2024)
Learning is a plan that is used as a guide in carrying out a learning process. The low student learning outcomes in the Geography subject can be seen from the scores that are below the KKM. This research aims to, 1 analyze the learning outcomes of the control class, 2 analyze the learning outcomes of the experimental class, 3 the influence of the Project Based Learning learning model on geography subjects at SMAN 14 Padang. The method used by researchers is quantitative with a type of correlational research using quasi experimental. Meanwhile, the sample was taken in the form of purposive sampling as many as 72 people, namely 36 students in class XIF 8 as the control class and 36 students in class XIF 10 as the experimental class, with data collection techniques in the form of observation, tests, questionnaires, documentation. The data analysis techniques that researchers use are: Normality, Homogeneity, Linearity, Partial correlation, simple linear regression and determination tests. The use of the Project Based Learning model has been proven to have a significant influence on student learning outcomes. The following research results in the experimental learning class using the Project Based Learning model are better than the control class which only focuses on the teacher, while to find out how much influence the Project Based Learning model has on student learning outcomes can be seen from the coefficient of determination R of 0.912 and the coefficient determination (R Square) is 0.831, which means that the influence given is 83.1% while 16.9 comes from outside.